Assessment of the Efficacy of an Alternative Regimen of Lomustine in Recurrent GBM – A Single Centre Experience. (1st October 2022) - Tan, Chevonne; Wong, Helen; Flint, Helen; May, Chloe; Shenoy, Aditya; Eswar, Chinnamani; Mehta, Shaveta
Abstract: AIMS: Lomustine (CCNU) based regimens are frequently used for recurrent glioblastoma multiforme (GBM). The usual CCNU regimen is 100-130mg/m2, day 1 x 6-weekly cycle for up to 6 cycles. Efficacy is limited, with median progression-free survival (PFS) approximating 1.0-3.0 months with higher haematological toxicities, particularly thrombocytopenia around 13-25%. The Clatterbridge Cancer Centre, UK, has adopted the regimen of 40mg once a day over 4 days x 4-weekly for up to 6 cycles. This study aims to identify the efficacy and toxicity profile of this regimen in recurrent GBM. METHOD: A retrospective analysis on 113 recurrent GBM patients, treated with single-agent CCNU as a second-line, between June 2016 and January 2020. Kaplan-Meier survival estimates identified PFS, PFS at 6 months (PFS6) and Overall Survival (OS) using SPSS v.27. Overall Responses were based on imaging or clinical assessment in patients with at least 2 CCNU cycles. SACT assessments and blood test records, using CTCAE v5.0 grading, identified clinical adverse events. RESULTS: We observed an 18.8% overall response rate with 2.4% partial response and 16.5% stable disease. There was a CCNU-specific 8-month median OS, 4-month median PFS, and 20.4%% PFS6. This regimen was well-tolerated. The most common toxicity was grade 1 fatigue (38.9%). The Grade 3 or 4 haematological toxicity was low with 12% thrombocytopenia and 2.7% neutropenia rates in patients. CONCLUSION: This study suggests a reasonable alternative to the usual regimen, offering improved tolerance, lower toxicity rates, and equivalent efficacy. We propose prospective studies comparing differing CCNU regimens to mitigate retrospective studies' limitations.